2017
DOI: 10.1016/j.oooo.2017.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Molar incisor malformation in six cases: description and diagnostic protocol

Abstract: In 5 out of 6 patients, severe health problems in the head and neck region early in life may have been associated with root malformation in molars and incisors. Patients with MIM need to be followed closely, and extractions should be planned at the right time to avoid unnecessary infection and pain in addition to orthodontic problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
83
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(94 citation statements)
references
References 22 publications
7
83
0
4
Order By: Relevance
“…The enamel of the clinical crowns typically appears unaffected, requiring radiographic examination to recognize the condition. Brusevold et al reported that the molars in two of their cases demonstrated demarcated opacities. These malformations most commonly involve the permanent first molars; however, primary second molars, permanent incisors, and rarely other teeth have been reported to also be affected .…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The enamel of the clinical crowns typically appears unaffected, requiring radiographic examination to recognize the condition. Brusevold et al reported that the molars in two of their cases demonstrated demarcated opacities. These malformations most commonly involve the permanent first molars; however, primary second molars, permanent incisors, and rarely other teeth have been reported to also be affected .…”
Section: Discussionmentioning
confidence: 95%
“…Since its initial description by Witt et al and the subsequent larger cases series by Lee et al, several reports and case series have been published documenting additional MIM cases . In the largest case series to date, Wright et al referred to this new dental phenotype as molar root‐incisor malformation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations